2020
DOI: 10.3390/jcm9061696
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Integrated Care Management on Dementia in Atrial Fibrillation

Abstract: Clinical outcomes of patients with atrial fibrillation (AF) can be improved by an integrated care approach. We analyzed whether adherence with the AF Better Care (ABC) pathway for integrated care management would reduce the risk of dementia in a nationwide AF cohort. Using the National Health Insurance Service database of Korea, 228,026 non-valvular AF patients were retrospectively evaluated between 2005 and 2015. Patients meeting all criteria of the ABC pathway were classified as the “ABC” group and those not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…This evidence, together with other data generated by secondary analyses of the studies included in this systematic review, which showed a significant impact of the ABC-pathway-adherent care in reducing the risk of dementia 32 and a significant reduction in health-care-associated costs, 33 strongly supports the recent changes introduced in the 2020 ESC AF clinical guidelines. 12 In these guidelines, there is a paradigm shift in approach, placing the patient at the centre of the physicians' action, not the disease itself.…”
Section: Discussionsupporting
confidence: 71%
“…This evidence, together with other data generated by secondary analyses of the studies included in this systematic review, which showed a significant impact of the ABC-pathway-adherent care in reducing the risk of dementia 32 and a significant reduction in health-care-associated costs, 33 strongly supports the recent changes introduced in the 2020 ESC AF clinical guidelines. 12 In these guidelines, there is a paradigm shift in approach, placing the patient at the centre of the physicians' action, not the disease itself.…”
Section: Discussionsupporting
confidence: 71%
“…1,6,7 Several post hoc analyses in various studies showed that the use of clinical care compliant to the ABC pathway criteria was associated with a reduction in risk of adverse outcomes. [8][9][10][11][12] In a recent cluster randomized trial, a mobile health-based ABC pathway management strategy significantly reduced the risk of the composite outcome of major clinical events. 13 Considering that AF patients with specific 'metabolic' comorbidities (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Three datasets were prospectively collected, 12 , 15–18 two were retrospective post hoc analyses of prospectively collected data 19 , 21 , 22 and two were registries or electronic health records. 13 , 14 , 20 , 23 Characteristics of the included studies are provided in Table 1 . Studies used data from around the world: South Korea ( n = 3), 13 , 14 , 23 China ( n = 2), 17 , 18 the Middle East ( n = 2), 15 , 16 Italy ( n = 1), 19 Europe ( n = 1), 20 the USA and Canada ( n = 2), 21 , 22 and the Balkans ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“… 13 , 14 , 20 , 23 Characteristics of the included studies are provided in Table 1 . Studies used data from around the world: South Korea ( n = 3), 13 , 14 , 23 China ( n = 2), 17 , 18 the Middle East ( n = 2), 15 , 16 Italy ( n = 1), 19 Europe ( n = 1), 20 the USA and Canada ( n = 2), 21 , 22 and the Balkans ( n = 1). 12 …”
Section: Resultsmentioning
confidence: 99%